Pengembangan Media Pembelajaran Matematika Berbasis Android Pada Materi Lingkaran Kelas VIII SMP - Rohmatullah, Indah; Afgani, Muhammad Win; Nizar, Harisman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
The development of android learning media becomes one of the alternatives in learning, especially in circle materials. The purpose of this research is to produce android-based learning media on valid and practical circle material. This type of research is development research with the ADDIE development model. The research subjects consisted of 17 students. This research data is obtained from questionnaires, interviews, and documentation. This research produces: (1) Learning media that are classified as valid based on validator comments and suggestions, (2) Learning media that are relatively practical based on the results of student comments and suggestions on questionnaires and interviews.